2019
DOI: 10.1002/aelm.201900537
|View full text |Cite
|
Sign up to set email alerts
|

MXene‐Reduced Graphene Oxide Aerogel for Aqueous Zinc‐Ion Hybrid Supercapacitor with Ultralong Cycle Life

Abstract: is much smaller for medium-and largeenergy storage systems. [9][10][11] Fortunately, constructing hybrid SCs (HSCs) that combine the merits of battery and SC with battery-type electrodes and capacitor-type electrodes is an intelligent way to improve the energy density of SCs. [12] The Li-ion and Na-ion-based HSCs that attempted to further improve the energy density of SCs have made certain progress, but these HSCs generally adopted organic electrolyte, which leads to serious safety issues. [13][14][15][16] Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
158
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 285 publications
(161 citation statements)
references
References 52 publications
3
158
0
Order By: Relevance
“…As shown in Fig. S1d and its inset, it is observed that the thickness of 2D MXene sheet is about 2.2 nm, which is close to the 1.5 nm thickness of monolayer MXene in our previous work [31]. As shown in XRD measure in Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As shown in Fig. S1d and its inset, it is observed that the thickness of 2D MXene sheet is about 2.2 nm, which is close to the 1.5 nm thickness of monolayer MXene in our previous work [31]. As shown in XRD measure in Fig.…”
Section: Resultssupporting
confidence: 84%
“…As a new group of 2D materials, the MXene is constructed of M N+1 X N T X structure, where the M represents an early transition metal such as Ti, and the X representing C and/or N element, and the T X meaning the terminal functional groups [26]. With its excellent metallic electrical conductivity, hydrophilic surface, and pseudocapacitance properties, the MXene has been explored as electrode materials for solar cells [27][28][29], zinc-ion capacitors [26,30], supercapacitors [31], or sensors [32]. In PSC application, it has also been reported that the PCE can be enhanced on the basis of the improved functional layers with MXene dopant.…”
Section: Introductionmentioning
confidence: 99%
“…The ZIC can still deliver a gravimetric specific capacitance of 112.2 F g −1 even at a high current density of 60 A g −1 , demonstrating its superior rate capability. Notably, an ultrahigh power density of 48.8 kW kg −1 with a correspondingly high energy density of 40.4 Wh kg −1 can be achieved at a current density of 60 A g −1 , which is the highest value among the ZICs [ 11,13,15,19,20,22,37–43 ] and ZIBs [ 12,44–48 ] reported recently. Considering ZIC with PC800 cathode can deliver twice the energy density and six times the power density of the ZIC with commercial YP‐50F cathode (50.2 Wh kg −1 and 7.4 kW kg −1 ), [ 49 ] we believe our ZIC with PC800 cathode is a promising device for practical energy storage applications.…”
Section: Resultsmentioning
confidence: 99%
“…An aqueous electrolyte-based battery-type zinc-ion hybrid supercapacitor was fabricated using MXene/rGO aerogel. [32] The zinc-ion hybrid supercapacitor was fabricated using porous Ti 3 C 2 T x MXene/rGO aerogel as the cathode, zinc Batteries & Supercaps foil as the anode, and M ZnSO 4 as the aqueous electrolyte. The MXene-rGO//Zn hybrid supercapacitor exhibited a high specific capacitance of 128.6 F/g and an energy density of 34.9 Wh/kg at a corresponding power density of 279.9 W/kg at a current density of 0.4 A/g.…”
Section: D Mxene Electrodes For Battery-type Hybrid Supercapacitorsmentioning
confidence: 99%